2009
DOI: 10.1097/mnh.0b013e328326092c
|View full text |Cite
|
Sign up to set email alerts
|

Developmental programming and hypertension

Abstract: Purpose of review There is a growing body of evidence linking adverse events or exposures during early life and adult-onset diseases. After important epidemiological studies from many parts of the world, research now focuses on mechanisms of organ dysfunction and on refining the understanding of the interaction between common elements of adverse perinatal conditions, such as nutrition, oxidants, and toxins exposures. This review will focus on advances in our comprehension of developmental programming of hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 154 publications
2
118
0
6
Order By: Relevance
“…24 The effect of prenatal smoking might be mediated by fetal reprogramming of the cardiovascular system in response to adverse global intrauterine growth conditions caused by placental insufficiency. 25 Hence, the findings of this study suggest that the implementation of strictly smoke-free environments, specifically at home, may be relevant to preserve cardiovascular health not only in the adult, but also in the pediatric, population. Although definite proof for this notion would require a long-term prospective interventional study, early prevention of tobacco smoke exposure is supported by several lines of reasoning.…”
Section: Simonetti Et Al Blood Pressure and Passive Smoking In Childrmentioning
confidence: 99%
“…24 The effect of prenatal smoking might be mediated by fetal reprogramming of the cardiovascular system in response to adverse global intrauterine growth conditions caused by placental insufficiency. 25 Hence, the findings of this study suggest that the implementation of strictly smoke-free environments, specifically at home, may be relevant to preserve cardiovascular health not only in the adult, but also in the pediatric, population. Although definite proof for this notion would require a long-term prospective interventional study, early prevention of tobacco smoke exposure is supported by several lines of reasoning.…”
Section: Simonetti Et Al Blood Pressure and Passive Smoking In Childrmentioning
confidence: 99%
“…18,19 A change in the endothelial function is an important factor for the development of cardiovascular diseases, particularly the decrease in circulating levels of nitric oxide leading to vasoconstriction and platelet aggregation. [19][20][21] Intrauterine growth restriction may lead to changes in renal morphology and physiopathology. Studies have demonstrated that children with a low nephron number tend to suffer changes in postnatal renal function, and consequently a fall in the glomerular filtration rate, and an accumulation of fluid and hypertension in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…2 Results from human epidemiological and animal studies demonstrate that the periconceptional, fetal, and early postnatal nutritional environments modify development of many systems in the offspring including the cardiovascular, metabolic, and endocrine systems. [3][4][5][6][7][8][9] These observations have led to the concept of a nutritional basis for the developmental origins of adult disease (developmental programming). 10,11 Deficient nutrition during pregnancy increases offspring morbidity and mortality as well as predisposes offspring to a wide range of chronic conditions in later life, such as diabetes, obesity, and cardiovascular disease (for review see [12][13][14].…”
Section: Introductionmentioning
confidence: 99%